The Journey by Radwa Ashour. (2nd October 2015) - Hartman, Michelle
Abstract : This contribution is a translation of the opening chapter of Radwa Ashour's The Journey: An Egyptian Woman Student's American Memoirs [ Al-Rihla: Ayyam Talibah Misriyah fi Amrika ] and a brief critical introduction to the author and her works. Never before published in English translation, this first chapter shows how The Journey is a memoir deeply engaged in politics, literature, and people's struggles. The work charts Ashour's years studying in the United States of the 1970s, where she would graduate from the W.E.B. Du Bois Department of Afro-American Studies and the English Department of the University of Massachusetts in 1975. A political progressive and leftist writer, critic, and activist, this memoir reflects not only on her own journey and struggles but those of the people she met and engaged with in the United States, especially Black Americans. Coming from an Egypt emerging from the Six Day War, Ashour links her generation in the Arab world to politically active people in America in a language and with a spirit that bring the 1960s and 1970s alive.